Emergency medical service personnel' post-traumatic stress disorder and psychological detachment: The mediating role of presenteeism - Liao, Dandan; Long, Yanqiong; Yu, Tao; Kang, Xiaoyan; Liu, Shulai; Yan, Jin; Zhang, AiDi (Frontiers in Public Health, 2023)
Background: Emergency medical service personnel are subjected to various stressors, which makes them more likely to develop post-traumatic stress disorder symptoms. Studies have shown that psychological detachment and presenteeism play a role at the level of post-traumatic stress disorder. There is no study to examine the relationship between psychological detachment, presenteeism, and post-traumatic stress disorder among emergency medical service personnel. Objective: The main objective of the study is to investigate the effects of presenteeism in explaining the relationship between psychological detachment and post-traumatic stress disorder among emergency medical service personnel. Design: A cross-sectional study was conducted among 836 emergency medical service personnel in 51 counties and cities in Hunan Province, China. Methods: They were anonymously investigated by using the Impact of Event Scale-Revised (IES-R), the Stanford Presenteeism scale-6(SPS-6), and the Psychological Detachment Scale. Statistic description, univariate analysis, pearson correlation, and structural equation model were adopted to analyze the data. Results: The mean score of IES-R, SPS-6, and the psychological detachment scale were 22.44±16.70, 15.13±4.20, and 11.30±4.24. Post-traumatic stress disorder was positively relevant with presenteeism (r=0.381, p<0.01), but negatively correlated with psychological detachment (r=-0.220, p<0.01). And presenteeism partially mediated the association between psychological detachment and post-traumatic stress disorder. Conclusions: The results show a high prevalence of post-traumatic stress disorder symptoms in EMS personnel, presenteeism can statistically significantly predict post-traumatic stress disorder symptoms. If hospital management can reduce the presenteeism of emergency medical service personnel, this will help them reduce post-traumatic stress disorder symptoms.